Acute low-dose bisphenol S exposure affects mouse oocyte quality - Prokešová, Šárka; Ghaibour, Kamar; Liška, František; Klein, Pavel; Fenclová, Tereza; Štiavnická, Miriama; Hošek, Petr; Žalmanová, Tereza; Hošková, Kristýna; Řimnáčová, Hedvika; Petr, Jaroslav; Králíčková, Milena; et al. (Reproductive toxicology (Elmsford, N.Y.), 2020)
Bisphenol S (BPS) is widely used to replace the known endocrine disruptor BPA in various products. We evaluated the effect of acute in vivo BPS exposure on oocyte quality, simulating the oral route of exposure via oral gavage. Eight-week-old ICR female mice (N = 15 per experimental group) were exposed to vehicle or BPS1-BPS4 (0.001, 0.1, 10, and 100 ng BPS x g bw-1 day-1, respectively) for seven days. Oocytes were isolated and matured in vitro. We observed that BPS exposure increased aberrant spindle formation in mature oocytes and induced DNA damage. Moreover, BPS3 significantly increased the chromatin repressive marks 5-methyl cytosine (5meC) and H3K27me2 in immature oocytes. In the BPS2 group, the increase in 5meC occurred during oocyte maturation. Transcriptome analysis revealed differential expression of early embryonic development transcripts in BPS2-exposed oocytes. These findings indicate that the biological effect of BPS is non-monotonic, affecting oocyte quality even at concentrations that are orders of magnitude below those measured in humans.
Keywords: Animals; Endocrine disruptors; DNA Damage; Female; Gene Expression Regulation, Developmental; ženské pohlaví; fenoly; Phenols; Oocytes; Epigenetics; sulfony; Meiotic spindle; Sulfones; těhotenství; oocyty; Histone modifications; stanovení celkové genové exprese; metylace DNA; Oocyte development; poškození DNA; Embryonic Development; DNA Methylation; Mice, Inbred ICR; DNA methylation; myši inbrední ICR; zvířata; embryonální vývoj; Pregnancy; vývojová regulace genové exprese; Gene Expression Profiling